Mine! : a story of not sharing - Persson, Klara (Berbay Publishing Pty Ltd, 2023)
Nico is coming over to play, but Sally doesn't want him to touch her toy squirrel. Or her train. Not her parking garage either. Sally's mom said to put the things she doesn't want to share in the wardrobe. As it turns out, there are quite a lot of things Sally doesn't want to share--including her mom. This fresh and funny approach to sharing shows just how complicated hiding all the things you love can be. In the end, it might be easier to give sharing a try. his fresh and funny approach to sharing shows just how complicated hiding all the things you love can be. In the end, it might be easier to give sharing a try. Maybe.